The livery halls of the city of London - Lucas, Anya (Merrell, 2018)
For more than 600 years the Livery Companies have played a leading role in commercial activities and social and political life in the City of London. These trade associations, each representing a particular craft or profession, were originally responsible for controlling, for example, wages and working conditions. As the Companies were established and incorporated by royal charter, largely in the 14th and 15th centuries, they began acquiring and adapting buildings from which to operate. The Companies' headquarters - the Livery Halls - gradually evolved from large medieval town houses to become an identifiable building type matched in scale and ambition only by the guild houses of northern European mercantile cities and the Venetian scuole. By the time of the Great Fire of London in 1666, there were at least 53 Livery Halls. Of the 40 Halls standing today, half remain on their medieval sites, but all have been rebuilt several times. To give only two examples: there have been six incarnations of Clothworkers' Hall on Mincing Lane and six Salters' Halls on three different City sites. This beautiful book is the first major exploration of these architecturally significant yet under-researched buildings.